Co-Evolutionary Algorithm for Motion Planning of Two Industrial Robots with Overlapping Workspaces. (21st January 2013) - Curkovic, Petar; Jerbic, Bojan; Stipancic, Tomislav
A high level of autonomy is a prerequisite for achieving robotic presence in a broad spectrum of work environments. If there is more than one robot in a given environment and the workspaces of robots are shared, then the robots present a dynamic obstacle to each other, which is a potentially dangerous situation. This paper deals with the problem of motion planning for two six-degrees-of-freedom (DOF) industrial robots whose workspaces overlap. The planning is based on a novel hall of fame - Pareto-based co-evolutionary algorithm. The modification of the algorithm is directed towards speeding-up co-evolution, to achieve real-time implementation in an industrial robotic system composed of two FANUC LrMate 200 i C robots. The results of the simulation and implementation show the great potential of the method in terms of convergence, robustness and time.